ORDER-DISORDER TRANSITION AND MICROWAVE DIELECTRIC-PROPERTIES OF BA(NI1/3NB2/3)O-3 CERAMICS - KIM, IT; KIM, YH; CHUNG, SJ (JAPAN J APPLIED PHYSICS, 1995)
Order-disorder transition of Ba(Ni1/3Nb2/3)O-3 ceramics was investigated using X-ray diffraction, transmission electron microscopy, and energy-dispersive spectroscopy, Before sintering samples were pre-fired at 1300 degrees C for 100 h to achieve higher chemical homogeneity. A transition from ordered to disordered state was observed at 1500 degrees C and the transition was accompanied by the formation of liquid phases. The chemical compositions of liquid phases were analyzed using energy-dispersive spectroscopy. Microwave dielectric properties of ordered and disordered samples were measured using the post resonator method and the transmission cavity method. Variations of dielectric properties such as relative permittivity, quality factor, and temperature coefficient of resonant frequency with sintering temperature were discussed in terms of order-disorder transition, liquid-phase sintering, defect concentration, and grain size.
Keywords: FREQUENCIES; PEROVSKITE